THE PHENOMENON OF FIXATION OF RIGHTS TO INDUSTRIAL APPLICATION OF THE RESULTS OF INTELLECTUAL ACTIVITY AT THE STAGE OF FUNDAMENTAL RESEARCH - F. A. Kurakov (Ekonomika Nauki)
Using the example of evolution of the genome editing technology, the phenomenon of fixing the rights to industrially applicable of the results of intellectual activity at the stage of fundamental research have been studied. Attention is drawn to the fact that the struggle for high added value of not yet created market high-tech product does take place not between industrial companies, but between centers of excellence (universities, research centers and start-ups). The case reviewed in the article makes it possible to cast doubt on the validity of the thesis that modern science exists outside national borders, having become a global network structure that carries out research by the forces of the world scientific community. It is concluded that the transition from an industrial economy to a postindustrial knowledge economy led to the transformation of the spatial cross-border organization of science and the model of interaction between scientists within the framework of open interdisciplinary research projects. This transformation is associated with the leading role of the business sector, supporting basic research, the results of which have obvious commercial projection.